2013
DOI: 10.1108/20426781311325041
|View full text |Cite
|
Sign up to set email alerts
|

Relationship quality in sports: a study in football teams and fitness centres

Abstract: Purpose -The purpose of this study is to identify the antecedents and dimensions of relationship quality (RQ) between customers and providers of athletic services. Design/methodology/approach -Data collection involved in-depth, personal interviews of fitness centre customers and year-ticket holders of football clubs in order to determine the similarities and differences between the two contexts. RQ is approached from the point of view of the customer since no other study has investigated that part of the dyad.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 74 publications
0
10
0
1
Order By: Relevance
“…According to Athanasopoulou et al (2013), relationship quality is a multidimensional concept measured by an array of interrelated factors. However, no consensus has been reached in literature on the factors that constitute relationship quality (Giovanis et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Athanasopoulou et al (2013), relationship quality is a multidimensional concept measured by an array of interrelated factors. However, no consensus has been reached in literature on the factors that constitute relationship quality (Giovanis et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The marketing for a club is to create an exchange in which members can exchange money for goods and services from the club (Perdue and Koenigsfeld, 2012). Earlier studies in the marketing literature of fitness clubs mainly focused on service quality and customer satisfaction as the antecedents of customer loyalty and membership retention (Athanasopoulou et al, 2013;Cha, 2019;Lim et al, 2016;Stauss et al, 2001). These studies focused on what fitness clubs as service providers can bring to members to influence members' behavioural intentions.…”
Section: Fitness Club Marketingmentioning
confidence: 99%
“…Previous studies indicated that effective knowledge management has been shown to enhance overall client satisfaction (Ku and Fan, 2009). Research studies have also indicated that club members' sports-related knowledge assists in establishing more enduring and satisfying relationships with fitness centres (Athanasopoulou et al, 2013). Moreover, customer satisfaction is associated with customers' expectations regarding their product/service experience (Churchill and Surprenant, 1982).…”
Section: Relationship Qualitymentioning
confidence: 99%
“…de (2002) ekonomik temelli sadakat programlarının müşteri sadakati veya tatminini arttırmak için yetersiz olabileceğini ifade etmiştir. Her ne kadar sadakat ve üyelik programları ilişki pazarlama taktiği olarak eleştiri alsa da spor kulüpleriyle ilgili bazı çalışmalarda (Athanasopoulou, Kalogeropoulou & Douvis 2013;Lee, Kunkel, Funk, Karg & McDonald, 2020) ilişki kurma ve sürdürmede önemli oldukları yönünde bulgular da mevcuttur.…”
Section: İlişki Pazarlamada Kullanılan Taktikler Ve Spordan öRneklerunclassified